Analisis Strategi Unit Pengumpulan Zakat (UPZ) Desa Pulau Melako dalam Meningkatkan Kesadaran Masyarakat Membayar Zakat - Siti Nurhaliza; Erwin Saputra Siregar (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the strategy of the Zakat Collection Unit (UPZ) of Pulau Melako Village in increasing public awareness to pay zakat. Although zakat has great potential in improving community welfare, the level of awareness of village communities towards zakat maal is still relatively low. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the UPZ of Pulau Melako Village has implemented several strategies such as direct socialization, empowerment of community leaders, and a personal approach to muzakki. However, obstacles such as lack of formal training for officers, limited use of information technology, and minimal infrastructure are still challenges in efforts to optimize zakat collection. The right and innovative strategy is needed to increase public awareness and participation in the obligation of zakat maal.